2003
DOI: 10.1046/j.1460-9592.2003.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cerebral oxygenation state in anaesthetized children using the INVOS 5100 cerebral oximeter

Abstract: The large range and the poor agreement of cerebral oxygenation values between the two oximeters makes it difficult to define a normal value. Cerebral oxygenation readings by these monitors, based on one single point measurement during anaesthesia, should be viewed with caution. Actually, there may be little indication for routine use of such monitoring during general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 24 publications
9
69
1
4
Order By: Relevance
“…In children, Dullenkopf et al 5 observed significantly lower TOI values (measured with the NIRO 300) compared to rSO2 values (measured with the INVOS 5100) and described a very large range in cerebral oxygenation values in children (rSO2: 59-95%; TOI: 48-85%). These results are consistent with our cerebral measurements in neonates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In children, Dullenkopf et al 5 observed significantly lower TOI values (measured with the NIRO 300) compared to rSO2 values (measured with the INVOS 5100) and described a very large range in cerebral oxygenation values in children (rSO2: 59-95%; TOI: 48-85%). These results are consistent with our cerebral measurements in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the adult and the pediatric sensor of INVOS 5100, Dullenkopf et al 5 observed also a difference of 10%, whereby the neonatal sensor, which is recommended in neonates, was not analyzed and compared until now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the previous clinical studies comparing devices have the drawback of rather narrow oxygenation range. For instance the NIRO 300 and INVOS 4100/5100 adult sensor have been compared several times showing comparable mean values during steady state, but all studies had very few if any rStO 2 values below 50% [38][39][40][41]. Regarding the difference between the INVOS adult and pediatric sensors, Dullenkopf et al found a similar mean difference of 11.3 ± 5.37% (SD) between the two sensors, while Pocivalnik found a mean difference of 10% between the NIRO 300 and the INVOS neonatal sensor [42], that has been shown to give similar values to the paediatric sensor [43].…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] While it may be appropriate to calibrate a probe for a specific patient group or even a specific organ of interest, it is not entirely clear how this calibration was made or if the result is closer to the "true" value.…”
Section: Agreementmentioning
confidence: 99%